T zone lymphoma: cellular origin and function - Hughes, Kelly Lynn, author; Avery, Anne, advisor; Ehrhart, EJ, committee member; Rovank, Joel, committee member; Page, Rodney, committee member; Dow, Steve, committee member (Colorado State University. Libraries, 2018)
The lymphoid system is exceedingly complex with specialized subsets of lymphocytes involved in both the innate and adaptive immune response. Lymphocytes are subdivided into T cells and B cells with lymphoproliferative disorders comprising a heterogeneous group of diseases arising from various lymphocyte subsets. Dogs are a natural model for studying cancer in humans with overlapping subtypes of lymphoproliferative disease seen in both species. We were particularly interested in characterizing lymphoma subtypes in dogs as a model for studying human disease progression. We believe characterization of lymphoma subtypes in dogs will contribute to enhanced understanding of the pathogenic mechanisms leading to the development of malignancy in both humans and dogs. T zone lymphoma (TZL) is a subtype of peripheral T cell lymphoma (PTCL) occurring in both humans and dogs. Determination of the cell-of-origin of PTCLs in humans has pointed to a subset of the larger disease, but up to half of these lymphomas cannot be further classified and are referred to as PTCL – not otherwise specified (PTCL-NOS). TZL has unique phenotypic characteristics including absence of the pan-leukocyte transmembrane protein, CD45, allowing for reliable identification by flow cytometry. CD45 has been found to be critical for T cell signaling through the T cell receptor (TCR). We hypothesized TZL has been derived from an activated, mature T cell. We used gene expression in an attempt to classify the cell-of-origin in TZL. Then we used in vitro systems to identify proliferative mechanisms, cytokine production, and immunosuppression at play in this disease. We determined TZL cells express genes associated with T helper 2 (Th2) and T regulatory (Treg) cells. We further confirmed that TZL cells do not proliferate through the TCR, likely due to their lack of CD45. We identified IL-2 may be involved in TZL signaling mechanisms. There are reports of TZL occurring with an opportunistic follicular mite infection, suggesting a component of immunosuppression with this disease. We thus anticipated TZL cells would have an immunosuppressive phenotype and inhibit normal T cells. Using in vitro methods, we were unable to confirm immunosuppression through production of TGF-β, inhibition of proliferation and inhibition of IFN-γ production. Finally, we observed older Golden retrievers having a higher frequency of cells with the same aberrant phenotype as TZL, but without evidence or suspicion of lymphoproliferative disease. We believe this finding resembles clonopathies of unknown significance in older human individuals, also with rare progression to disease. We now believe TZL is derived from a Th2 or Treg-like mature T cell which may be responsible for the indolent nature of this disease due to the tolerant behavior of those T cell subsets. Furthermore, inducing proliferation in this disease was challenging, which is consistent with slowly progressive biologic behavior. Expression of immunosuppressive molecules may also contribute to the indolent nature of this disease. While we were not able to observe immunosuppression in vitro, it is reasonable to assume there may be in vivo mechanisms of immunosuppression resulting in clinical manifestations seen in TZL. Characterization of cell-of-origin of this disease, neoplastic cell function, along with recognition of a pre-neoplastic state, contributes to enhanced understanding of the pathogenesis of lymphoproliferative diseases in both humans and dogs.
Zip file contains supplementary tables.
Keywords: lymphoma; T zone lymphoma; T-cell; canine